Nonexpansivity of the Newton's Cradle Impact Law. Issue 1 (21st October 2015) - Leine, Remco I.; Winandy, Tom
Abstract The 3‐ball Newton's cradle is used as a stepping stone to divulge the structure of impact laws. A continuous cone‐wise linear impact law which maps the pre‐impact contact velocities to the post‐impact contact velocities is proposed for the 3‐ball Newton's cradle. The proposed impact law is kinematically, kinetically, and energetically consistent. It reproduces all the classical experimental outcomes. Moreover, the impact law has the mathematical property of being non‐expansive. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)